KETERAMPILAN BERKOMUNIKASI SISWA MENGGUNAKAN METODE ACTIVE DEBATE DALAM PEMBELAJARAN PPKn DI SMA NEGERI 9 PONTIANAK - Rini Musdalifah; Rum Rosyid; Thomy Sastra Atmaja (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to find out the communication skills of students using active debate methods in PPKn learning at SMA Negeri 9 Pontianak. This research uses qualitative approach. Data collection techniques in this study are using observation techniques, interviews, and documentation studies, the research subject is grade XI IIS2 with a total of 30 students. The research process uses 1 class with 2 meetings. The results of data analysis showed that students' communication skills at meeting 1 before getting active debate method treatment with the 2nd meeting getting active debate method treatment were different. Proven by the average results of communication skills of students at meeting 1 is 51.33%. While at the 2nd meeting using active debate method increased to 75.99%. meetings 1 and 2 averaged 63.66% of students' communication skills including strong criteria. This is a difference in students' communication skills using active debate methods in PPKn learning in grade XI IIS2. Therefore, it can be concluded that the active debate method provides communication skills in class XI IIS2 Pontianak, especially ppkn.Keywords: Student Communication Skills, Active Debate Method, PPKn Learning, Senior High School 9 Pontianak